A problem of power supply of microprocessor-based protective relays at emergency mode - Gurevich, V. (Електротехніка і електромеханіка, 2007)
The paper discusses a problem of power supply for microprocessor-based protective relays in a substation with AC and DC auxiliary voltage in an emergency mode. The paper recommends application of power capacitors and supercapacitors instead of UPS as energy storage elements for shorttime duration feeding of protective relays in emergency modes. Розглянуто проблему електроживлення мікропроцесорних пристроїв релейного захисту на підстанціях зі змінною та постійною оперативною напругою в аварійних режимах. Рекомендовано застосовувати конденсатори великої ємності та суперконденсатори як накопичувачі енергії для короткочасного живлення захисних реле в аварійних режимах. Рассматривается проблема электропитания микропроцессорных устройств релейной защиты на подстанциях с переменным и постоянным оперативным напряжением в аварийных режимах. Рекомендуется использовать конденсаторы большой емкости и суперконденсаторы в качестве накопителей энергии для кратковременного питания защитных реле в аварийных режимах.